Pelatihan Penyusunan Laporan Keuangan Sederhana bagi Pelaku Usaha Mikro Desa Brangjan Kecamatan Ungaran Barat Semarang - Agus Ariawan; Happy Herawati (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
Micro, Small and Medium Enterprises (MSMEs) play an important role in economic growth, but often face obstacles in good financial recording and reporting. Many micro-entrepreneurs in Brangjan Village, West Ungaran, Semarang, do not yet have an adequate understanding of the preparation of systematic financial reports, making it difficult to manage finances and access funding from financial institutions. This community service activity aims to improve the understanding and skills of micro-entrepreneurs in preparing simple financial reports based on easy-to-apply accounting principles. The methods used in this training include counseling, direct practice, and assistance in recording financial transactions, profit and loss reports, and simple balance sheets. Participants are also introduced to the use of technology or digital financial recording applications that can assist in managing their businesses. The results of this training show that most participants experienced an increase in understanding in financial recording, and were able to prepare simple financial reports independently. This training is expected to provide long-term benefits for micro-entrepreneurs in developing their businesses more professionally and sustainably.